Emotional Impact and Perceived Effectiveness of Text-Only versus Graphic Health Warning Tobacco Labels on Adolescents. (2019) - Margalhos, Pedro; Esteves, Francisco; Vila, Jaime; Arriaga, Patrícia
Abstract: The study of smoking in adolescence is of major importance as nicotine dependence often begins in younger groups. Tobacco health warnings have been introduced to inform people of the negative consequences of smoking. This study assessed the emotions and perceived effectiveness of two formats of tobacco warnings on adolescents: Text-only versus graphic warning labels. In addition, we analyzed how emotions predicted their perceived effectiveness. In a cross-sectional study, 413 adolescents (131 smokers, 282 non-smokers) between 13–20 years of age rated their emotions (valence and arousal) and perceived effectiveness towards a set of tobacco warnings. Results showed that graphic warnings evoked higher arousal than text-only warning labels ( p = .038). Most of the warning labels also evoked unpleasantness with smokers reporting higher unpleasantness regarding text-only warnings compared to non-smokers ( p = .002). In contrast, perceived effectiveness of the warnings was lower in smokers than in non-smokers ( p = .029). Finally, high arousal and being a non-smoker explained 14% of the variance of perceiving the warnings more effective. Given the role that warnings may play in increasing health awareness, these findings highlight how smoking status and emotions are important predictors of the way adolescents consider tobacco health labels to be effective.